The story of the New England whalers - Stein, R. Conrad; Dunnington, Tom (Chicago : Childrens Press, 1982)
The history of whaling in New England from the early eighteenth century to its decline when oil was discovered in mid-nineteenth century.
Keywords: Whaling -- Juvenile literature; Whalers (Persons) -- New England -- Juvenile literature; Whaling -- New England; New England -- Economic conditions